Port of Spain Riot, 23rd March, 1903, Trinidad, B.W.J. [sic] - (:unkn) unknown (My University, 2010)
Photo showing the scene outside the Red House building located in Port of Spain, Trinidad on the day of the March 23rd, 1903 water riots. Several persons are seen standing outside the building watching the fire.
Colour: Black and White; Style: Landscape; Other: Bordered, Undivided.
Keywords: Trinidad and Tobago; Postcards; Trees--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Riots--Trinidad and Tobago; 1904; Crowds--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Horses--Trinidad and Tobago; Streets--Trinidad and Tobago; Architecture--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Historic buildings--Trinidad and Tobago